Crystal structure of norgestimate, C23H31NO3. Issue 4 (28th September 2016) - Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of norgestimate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Norgestimate crystallizes in space group P 21 21 21 (#19) with a = 11.523 67(9), b = 16.130 72(20), c = 22.247 93(20) Å, V = 4135.56(7) Å 3, and Z = 8. There are two independent molecules in the asymmetric unit, with opposite conformations of the acetate groups. Molecule 2 is 7.3 kcal mole −1 lower in energy than molecule 1, and is in the minimum energy conformation. The hydroxyimine groups form O–H⋯O hydrogen bonds to the acetate carbonyl groups, resulting in two separate C(15) chains along the b -axis. The powder pattern is included in the Powder Diffraction File ™ as entry 00-064-1503.